THE EFFECTS OF USSR STRATEGY, METACOGNITIVE STRATEGY, AND READING HABIT ON READING COMPREHENSION ACHIEVEMENT - Syafitri, Meity (Jurnal Ilmiah Bina Bahasa, 2019)
Reading is one of the language skills which has an important role for the people because by reading people can get much information which they need. However, reading is not a simple activity. English reading is still a challenging task for Indonesian students. Therefore, a certain strategy may be used for improving students? reading achievements. Using the USSR and Metacognitive strategies, this study aimed at improving the students? reading comprehension achievement and finding out whether or not there was interaction among both strategies and students? reading habit toward reading comprehension achievement. The population of this study is the tenth graders. Sixty tenth graders were selected as the sample and equally divided into experiment group 1 and experiment group 2. Next, both groups were tested before and after the treatment. Using paired sample t-test statistics, the results showed that the students? reading comprehension achievement was significantly improved. The result of two way ANOVA showed that there was interaction (0.009).